In-Vitro Plantlet Regeneration and Agrobacterium-Mediated Gene Transformation of Carica Papaya L. Cv. Eksotika - Panjaitan, Syaiful Bahri (2006)
The study was conducted at the In Vitro Laboratory, Institut Pertanian Persekitaran Terkawal (IPPT), Faculty of Agriculture and Molecular and Cell Biology Laboratory, Faculty of Biotechnology and Biomolecular Sciences, Universiti Putra Malaysia, Serdang, Selangor. The main objectives of the study were to develop in-vitro plantlet regeneration systems and to carry out preliminary studies of Agrobacterium-mediated gene transformation of Carica papaya L. cv. Eksotika.